Islamic Branding and Product Ingredients: Non-Muslim Dilemma in Consuming Halal Meat - Anggraeni, Erike; Normasyhuri, Khavid; Wisnu Kusuma, Tri Atmaja Pramudita (Politeknik Negeri Bandung, 2024)
Consuming halal foods is unarguably a matter of need for every Muslim. Today, the interest in eating halal cuisine is even growing not only for Muslims but also non-Muslims because the COVID-19 pandemic, which emerged lately, has emphasized a lack of people’s health and sanitation. This study intends to investigate how non-Muslim customers' perceptions of Islamic branding affected their purchase decisions of halal food during the COVID-19 pandemic. A number of 500 non-Muslim respondents took part in this study by answering questions for this quantitative research. The data was then analyzed using SmartPLS 3.0. The results revealed that there was a significant correlation between Islamic branding and product ingredients and non-Muslims intention of choosing halal food during COVID-19. This tendency is due to the fact that halal food is guaranteed qualified since it is delicious and prepared in clean and healthy way.